Proliferation of porang (Amorphophallus muelleri Blume) from bulbils and leaf cutting treated by NAA and BA - Putri, Ayu Diah Putu Laksmi; Wiendi, Ni Made Armini; Santosa, Edi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Javanese konjac or iles-iles (Amorphophallus muelleri Blume, Araceae) is a tuber crop native to Indonesia as a source of carbohydrat, also contains a lot of glucomannan, which has high economic value as a raw material in industry. The study aimed to develop the propagation method of A. muelleri from bulbils and leaf cuttings through the plant growth regulator (PGR) application of α-naphthaleneacetic acid (NAA) and benziladenin (BA). The research was conducted from August 2020 to December 2021 at IPB University, Bogor. The study consisted of three experiments based on the type of propagation material. Each experiment used a randomized complete block design with three factors, i.e., NAA concentrations (0, 2, and 4 mg L-1), BA concentrations (0, 5, 10, and 15 mg L-1), and propagation materials (Experiment 1: small, medium, large bulbils; Experiment 2: immature and mature peak leaflet cuttings; Experiment 3: immature and mature base leaflet cuttings). The results showed that there was an interaction of three factors in the bulbils and PGR application, which had a significant effect on the percentage of axillary shoot proliferation and growth. In Experiment 2, PGR application was unable to regenerate peak leaflet cuttings, whereas in Experiment 3 PGR encouraged base leaflet cuttings to form shoots, roots, and bulbils, especially at concentrations of 2 mg L-1 NAA+15 mg L-1 BA and 4 mg L-1 NAA+15 mg L-1 BA. Keywords: α-naphthaleneacetic acid, benziladenin, iles-iles, Javanese konjac, plant growth regulators